Distribution of wealth: A critique of Rawlsian liberalism. - Manyeli, Louis. (University of Ottawa (Canada), 2001)
Can we distribute resources such that nearly all people can carry out their life plans? By sheer luck, some people happen to be naturally endowed, and their talents make them well off. Others, by brute bad luck, find themselves being naturally disadvantaged or less talented, and these conditions make them worst off. How can the frustrating and devastating situation of the latter group be remedied? John Rawls, a prominent contemporary liberal egalitarian, thinks that a fair distribution of wealth can be achieved if people choose his two principles of justice. With the two principles in operation, Rawls maintains, people can retain their basic liberties while committing themselves to social duties, duties that require them to assist the least fortunate members of a well-ordered society. Rawls thinks that liberty and equality are reconcilable in his theory. I trace the background to Rawls in Rousseau and Kant, and show how liberty and equality must be understood and significantly interconnected. The present work is primarily a critique of Rawls' theory of justice in regard to its position on the distribution of wealth, that is, Rawls' principle of distributive justice. My purpose is to show that Rawls' principle does not go far enough in the needed direction of redistribution, to provide what disadvantaged people genuinely require as a matter of fairness and actual opportunity; and further that this limitation in Rawls' position on economic distribution works to undermine Rawls' principle of equal liberty, as it applies in the real world. I also show that Rawls' critics, such as Nielsen, Sandel, Nozick, van Parijs, Dworkin and Kymlicka fail to provide a preferable solution to the problem of the distribution of wealth. I make a case for a commitment to the extensive redistributive tax measures needed to insure truly universal education as the condition of equal opportunity. I argue that this proposal is, in fact, consistent with egalitarians' aim to achieve equality, and consistent with Rawls' equal opportunity principle. Although Hegel has hardly figured as a model for egalitarians in the history of political philosophy, I argue that he is a model for egalitarians, and that he offers a preferable solution to the antinomies of contemporary thought. This means that he is a potential interlocutor in these contemporary debates. The central claim which I try to establish is that the Hegelian concern to reconcile individual freedom with new forms of community is germane to his vindication of economic rights. To put my point another way, I argue that contrary to the liberals' formalistic preoccupation with rights, interests, and rational preferences, Hegel correctly urges us to return to the sort of full-bodied philosophical anthropology that can specify the fundamental moral, economic, and political needs of human beings.
Keywords: Philosophy.